2016
DOI: 10.1093/rheumatology/kew357
|View full text |Cite
|
Sign up to set email alerts
|

Abatacept reduces disease activity and ultrasound power Doppler in ACPA-negative undifferentiated arthritis: a proof-of-concept clinical and imaging study

Abstract: to 2.01(0.81) at 6 months and to 1.78(0.95) at 12 months. DAS44 remission rates were 6/20 (30%; 95%CI 15%, 51%) at 6 months and 8/20 (40%; 95%CI 22%,62%) at 12 months.A striking decrease in median(IQR) total PD score was noted from 10(4,23) at baseline to 3(2,12) and 3(0,5) at 6 and 12 months respectively. Conclusions:This report is a first in potentially identifying an effective therapy, abatacept monotherapy, for poor prognosis ACPA negative UA, supported by a clear reduction in US PD. These data justify eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…There are also lines of evidence implicating T-cell-independent effect of abatacept on monocytes/macrophages and osteoclasts [17,18]. In fact, abatacept exerted therapeutic effect in animal models without CD4 T cells [19], and in patients with seronegative arthritis as well [20]. Further clinical and basic studies are required to understand the effect of abatacept on the pathogenesis of joint inflammation and ACPA production in RA, which is important for optimizing the use of abatacept for the treatment of RA.…”
Section: Discussionmentioning
confidence: 99%
“…There are also lines of evidence implicating T-cell-independent effect of abatacept on monocytes/macrophages and osteoclasts [17,18]. In fact, abatacept exerted therapeutic effect in animal models without CD4 T cells [19], and in patients with seronegative arthritis as well [20]. Further clinical and basic studies are required to understand the effect of abatacept on the pathogenesis of joint inflammation and ACPA production in RA, which is important for optimizing the use of abatacept for the treatment of RA.…”
Section: Discussionmentioning
confidence: 99%
“…Undifferentiated arthritis (UA) is defined as an inflammatory arthritis not satisfying classification criteria for rheumatoid arthritis (RA) (1)(2)(3) or peripheral spondyloarthritis (pSpA) (4), including psoriatic arthritis (PsA) (5). UA represents 33-35% of patients in early arthritis clinics, usually as mono-or oligoarthritis.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we have demonstrated that infiltrating inflammatory cells in RA synovium may modulate not only inflammation but also bone and cartilage destruction [11]. A therapeutic strategy against synovitis may have the potential to inhibit inflammation, joint pain (arthralgia), and the degeneration of bone and cartilage tissues [9][10]. In this study, we focused on the synovitis to develop a new therapeutic strategy for RA.…”
Section: Introductionmentioning
confidence: 99%
“…In RA synovium, large numbers of infiltrating T cells, macrophages, osteoclast precursor cells and synovial fibroblasts can be seen. It has been demonstrated that infiltrating lymphocytes and macrophages in RA synovial tissue produce excessive levels of pro inflammatory cytokines, such as tumor necrosis factor (TNF)-, interleukin (IL)-1 and IL-6 [4][5][6][7][8][9][10][11][12][13]. These cytokines form a network and are key participants in the pathogenesis of arthritis.…”
Section: Introductionmentioning
confidence: 99%